La dimension existentielle dans la construction du problème en recherche doctorale - Constantin Xypas; Jean-Yves Robin (Nantes Université, 2010)
Observation of graduate students in education and the social sciences in particular reveals that the existential factor is a complex phenomenon. It mobilizes interest and leads to inquiry; but simultaneously, it causes intellectual resistance and inhibits the rupture with common sense (misconceptions). It therefore hinders the construction of true scientific inquiry.